The effect of ZnO growth temperature on the memristive behaviour of Hybrid ZnO graphene thin film / Tengku Norazman Tengku Abd Aziz ...[et al.] - Tengku Abd Aziz, Tengku Norazman; Rosli, Aimi Bazilah; Mohd Yusoff, Marmeezee; Herman, Sukreen Hana; Zulkifli, Zurita (UiTM Press, 2018)
Hybrid ZnO-Graphene devices have revealed a stable switching cycle compared to ZnO devices. They have better memristive performance and are suitable in non-volatile memory applications. Here, we report the effect of ZnO growth temperature on the memristive effect of ZnO and hybrid ZnOGraphene thin films. We show the electrical, optical and morphological properties of the devices using Thermal Chemical Vapour Deposition (TCVD) and Water Bath methods. The relationship between ZnO morphological structure and carrier mobility is discussed. Additionally, the effect of Graphene insertion is shown in the number of switching cycles. It was found that the ZnO thin film deposited at 350˚C showed high resistance ratio of about 3.17 due to the defects present in the crystal structure. On the other hand, nanoparticles in 450˚C and 550˚C samples resulted in thicker films that reduced the memristive window to 1.9 and 2.6 respectively. Hybrid devices exhibited increased stability at switching cycle 4 compared to ZnO devices.